天下兴亡，匹夫有责：顾炎武与梁启超思想比较研究 = The rise and fall of the “Tianxia” is the responsibility of every “Pifu”: A comparative study of the political thought of Gu Yanwu and Liang Qichao - 刘倇伽 Lew, Wan Jia (Nanyang Technological University, 2025)
在中国思想史上，顾炎武与梁启超虽身处不同的历史时期，但他们在“天下兴亡，匹夫有责”这一命题上形成了深刻的思想共鸣。顾炎武提出此言论时，强调士大夫阶层对于天下兴亡的直接责任，而梁启超则在全社会范围内推广了这一理念，将责任主体扩大至全民，并强调民众在国家中的主体性。这一思想的阐发与继承，不仅展现了个人与国家之间的紧密联系，也反映了不同时代中国知识分子对社会危机的应对策略与思想转变。 本篇论文将通过分析顾炎武《日知录·正始》及梁启超《饮冰室合集·痛定思言》中对于“天下兴亡，匹夫有责”的论述，比较二人的儒学观，并结合他们对“天下”与“匹夫”概念的不同寄托，以论证顾炎武的原意是希望士大夫承担起捍卫儒家文化的重担，而梁启超则更强调民众作为国家主体之一的政治观。 In the history of Chinese thought, although Gu Yanwu and Liang Qichao lived in different historical periods, they formed a profound ideological resonance on the proposition that “The rise and fall of the ‘Tianxia’ is the responsibility of every ‘Pifu’” (天下兴亡，匹夫有责). When Gu Yanwu proposed this idea, he emphasized the direct responsibility of the scholar-official class in maintaining the stability of the state. In contrast, Liang Qichao expanded this concept to the entire society, extending the responsibility to all citizens and highlighting the role of the people as the main body of the nation. The development and inheritance of this idea not only demonstrate the close relationship between individuals and the state but also reflect the responses and ideological transformations of Chinese intellectuals in different historical contexts when facing social crises. This paper analyses Gu Yanwu’s discussion in Rizhi Lu: Zhengshi (《日知录·正始》) and Liang Qichao’s interpretation in Yinbing Shi Heji: Tongding Zuiyan (《饮冰室合集·痛定思言》) regarding “The rise and fall of the ‘Tianxia’ is the responsibility of every ‘Pifu’”. It compares their Confucian perspectives and examines their differing interpretations of the concepts of “Tianxia” (天下) and “Pifu” (匹夫). Through this analysis, this paper argues that Gu Yanwu’s original intention was to urge scholar-officials to take up the responsibility of preserving Confucian cultural traditions, whereas Liang Qichao emphasized a more modern political perspective in which the people serve as the core entity of the nation.